Three New Species of Opistholeptus Bergroth from West Africa (Heteroptera: Lygaeidae). - Slater, James Alexander (Beiträge zur Entomologie = Contributions to Entomology, 1953)
Nomenklatorische Handlungen chinai Slater, 1953 (Opistholeptus), spec. n. jordani Slater, 1953 (Opistholeptus), spec. n. parvus Slater, 1953 (Opistholeptus), spec. n.